2015
DOI: 10.3233/bme-151518
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial, anti-inflammatory, and antioxidant effects of Yinzhihuang injection

Abstract: Abstract. The Yinzhihuang injection, a traditional Chinese medicine, has been the recent target of increasing interest due to its anti-inflammatory properties. The molecular basis by which Yinzhihuang injection could cure Riemerella anatipestifer (RA) serositis in ducks is unclear. This study evaluated the antibacterial, anti-inflammatory and antioxidant effects of Yinzhihuang injection, using disease models of RA-induced infectious serositis in ducks and heptane-induced inflammation in mice and rats. The duck… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 28 publications
(32 reference statements)
1
3
0
Order By: Relevance
“…Further examination involved GO enrichment analysis of the targeted mRNAs, revealing their predominant involvement in inflammatory responses and other biological processes. These findings align with a study conducted by Liu et. al.…”
Section: Plos Onesupporting
confidence: 93%
See 2 more Smart Citations
“…Further examination involved GO enrichment analysis of the targeted mRNAs, revealing their predominant involvement in inflammatory responses and other biological processes. These findings align with a study conducted by Liu et. al.…”
Section: Plos Onesupporting
confidence: 93%
“…(2015), which demonstrated that R . anatipestifer infection promotes NOS2 activity [ 8 ]. Consequently, the upregulation of NOS2 expression triggers the upregulation of other genes, particularly those associated with Th1 and Th2 responses, while showing limited impact on Th17-related genes in the context of R .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once R. anatipestifer invades the host body, the bacterium multiplies rapidly and reaches various tissues and organs through the blood, causing systemic serositis. The main clinical anatomical manifestations of R. anatipestifer infection are fibrinous pericarditis, perihepatitis, airsacculitis, and meningitis ( Liu et al, 2015 ; Fernandez et al, 2018 ; Wang et al, 2019a ; Yang et al, 2019 ). Duck infectious serositis was first reported in Long Island, New York in 1932 and subsequently spread throughout Australia, the United Kingdom, the former Soviet Union, and other countries ( Hendrickson and Hilbert, 1932 ).…”
Section: Introductionmentioning
confidence: 99%